EFFORTS TO IMPROVE STUDENTS’ SPEAKING ABILITY ON THE THEME OF “KEGIATANKU” THROUGH ROLE PLAY - Ardiwati (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2020)
This research was conducted as a result of the lack of students' ability to speak in the learning process, such as telling a story and asking and answering teacher questions. Role play was expected to improve students' speaking ability. This research was conducted at SDN 005 Pulau Kumpai, Kecamatan Pangean. The instrument of this research was the observation sheet for obtaining information about students' speaking ability. The results revealed that students 'speaking ability in the first cycle was 67.05 which was in sufficient category. Unfortunately, this result did not reached the expected indicators, so the research was revised and continued to cycle II. In this cycle, the students' speaking ability achieved an average percentage of 75.29 which was included in good category. Students were enthusiastic to participate in learning due to having the motivation to show their best to other students and teachers in front of the class. Based on the results of this study, it can be concluded that the students’ speaking ability for the theme of “Kegiatanku” at grade 1 SDN 005 Pulau Kumpai, Kecamatan Pangean increased through role play method.